STRATEGI PENGEMBANGAN USAHA DAGANG BERKAH GROUP UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT DI KELURAHAN SITIREJO II ,KEC. MEDAN AMPLAS - Fachreza Aulia Lubis2; Abdi Zurianda,; Swinda Sitorus (Cattleya Darmaya Fortuna, 2022)
The purpose of this study is to formulate a strategy in developing the blessing group trading business to increase people's income in the village of Gang Aman equation no 48, Sitirejo 11 sub-district, kec. It is hoped that Medan Amplas will be able to open jobs in the future through a business development strategy so that it can increase people's income later. Method of data analysis using SWOT analysis. The results of the study indicate that alternative strategies that can be used in developing a business are improving services and human resources.